Sons of fortune - Archer, Jeffrey (Pan books, 2002)
In Hartford, Connecticut, in the late 1940s, twin brothers are accidentally separated at birth. One brother grows up to be a war hero in Vietnam and a successful 1990s bank executive, while the other distinguishes himself as a lawyer and politician. When both men decide to run for governor, they learn the truth about their kinship-- and must face its tragic consequences.